E-Fitness Buddy - Abdullah, Muhammad Amir Imran; Armi Riffa, Mohamad Faiz; Abd Rahim, Nurul Zahirah (2020)
Many people are concerned with their bodies nowadays but struggled to visit the gym regularly due to their hectic daily schedules. In the era of technology, fitness application is getting more approval and praise for assisting the user in performing their workout routine independently. Unfortunately, workout without expert guidance can caused injuries since users who are lacking knowledge, unable to identify the most suitable routine to perform based on their body mass and goals. E-Fitness Buddy is a prototype of a mobile application that will recommend a suitable workout routine which reflects the user’s preference and need. E-Fitness Buddy is designed to keep track the user’s progress and henceforth users will be motivated by knowing their performance based on the recommended workout routine. However, it is recommended to consider on more related criteria to recommend on the workout routine to the user.